2002
DOI: 10.1034/j.1399-6576.2002.460615.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lung recruitment maneuver and positiveend‐expiratory pressure on lung volume, respiratory mechanics and alveolar gas mixing in patients ventilated after cardiac surgery

Abstract: Positive end-expiratory pressure is required after a lung recruitment maneuver in patients ventilated with high FiO2 after cardiac surgery to maintain lung volumes and the improved oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
0
16

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 39 publications
10
83
0
16
Order By: Relevance
“…Esse aumento na oxigenação depois da MRA também sugere um melhor acoplamento entre a ventilação e a perfusão pulmonar. Há alguma controvérsia quanto a maior ou menor efetividade da MRA para corrigir a hipoxemia, quando aplicada de forma isolada ou em conjunto com a PEEP ou a PEEP de maneira isolada em procedimentos cirúrgicos cardíacos e pulmonares 5,11,15,16 . Em investigação pregressa, também em pacientes no pós-operatório de intervenção cirúrgica cardíaca, demonstrou-se que a aplicação progressiva da PEEP até 15 cm de H 2 O foi efetiva em aumentar a oxigenação com mínimos efeitos hemodinâ-micos negativos 5 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Esse aumento na oxigenação depois da MRA também sugere um melhor acoplamento entre a ventilação e a perfusão pulmonar. Há alguma controvérsia quanto a maior ou menor efetividade da MRA para corrigir a hipoxemia, quando aplicada de forma isolada ou em conjunto com a PEEP ou a PEEP de maneira isolada em procedimentos cirúrgicos cardíacos e pulmonares 5,11,15,16 . Em investigação pregressa, também em pacientes no pós-operatório de intervenção cirúrgica cardíaca, demonstrou-se que a aplicação progressiva da PEEP até 15 cm de H 2 O foi efetiva em aumentar a oxigenação com mínimos efeitos hemodinâ-micos negativos 5 .…”
Section: Discussionunclassified
“…Tusman e col. registraram valores semelhantes de pressão nas vias aéreas na melhora da oxigenação após anestesia para cirurgia geral. Há poucos relatos da utilização da MRA em procedimentos cirúrgicos cardíacos 11,12 . Dyhr e col. 6 definiram a MRA como sendo a aplicação de quatro insuflações sustentadas com pressão nas vias aéreas de 45 cmH 2 O por 10 segundos cada, na modalidade CPAP do ventilador.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…The hypoxemia conditions in these patients occurs due to intrapulmonary shunt fraction caused by collapsed alveoli [21,22]. According to Neves et al [19], ARM is particularly indicated in clinical situations that can cause alveolar collapse, such as anesthesia, sedation and neuromuscular blockade, as well as to disconnect the patient from the mechanical ventilation.…”
Section: Indicationsmentioning
confidence: 99%